ANALISIS EFEKTIVITAS PENYALURAN PEMBIAYAAN KPR SYARIAH BERSUBSIDI DI BANK BTN KC SYARIAH MEDAN - maryam batubara (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine whether the distribution of subsidized Sharia mortgage financing to Low-Income Communities during the COVID-19 pandemic is effective or not, and can determine the percentage of effectiveness in the distribution of subsidized Sharia mortgage financing at BTN Syariah for the community, especially Low-Income Communities (MBR). . Considering that during the COVID-19 period, there are many people whose income is small due to the impact of COVID-19. In this study, the authors use quantitative research methods through the research approach of Field Research and Library Research. Researchers used primary data and secondary data, with data collection techniques in the form of questionnaires, interviews, and documentation studies directly coming to Bank BTN Syariah and interviewing existing sources. The researcher also distributed questionnaires to 94 respondents who had been determined from customer data who participated in the subsidized Sharia mortgage program during the COVID-19 pandemic using the slovin method and Non Probability Sampling which was used Accidental Sampling. Meanwhile, to measure the percentage level of effectiveness in the distribution of subsidized Sharia mortgage financing, the author uses the Artificial Neural Network (ANN) method. The results of this study indicate that the distribution of subsidized Sharia mortgage financing at BTN KC Syariah Medan during the COVID-19 pandemic is effective. With an effectiveness level of 0.9999 or 99.99%, which shows that the distribution of subsidized Sharia mortgage financing at BTN KC Syariah Medan during the COVID-19 pandemic to Low-Income Communities (MBR) is said to be effective.